2003
DOI: 10.1002/cphc.200390063
|View full text |Cite
|
Sign up to set email alerts
|

An Ab Initio Study on the Mechanism of the Atmospheric Reaction NH2+O3→H2NO+O2

Abstract: The atmospheric reaction NH2 + O3-->H2NO + O2 has been investigated theoretically by using MP2, QCISD, QCISD(T), CCSD(T), CASSCF, and CASPT2 methods with various basis sets. At the MP2 level of theory, the hypersurface of the potential energy (HPES) shows a two step reaction mechanism. Therefore, the mechanism proceeds along two transition states (TS1 and TS2), separated by an intermediate designated as Int. However, when the single-reference higher correlated QCISD and the multiconfigurational CASSCF methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
11
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
3
11
0
Order By: Relevance
“…Therefore, this work gives us further indication that the experimental results obtained on the kinetic study of the NH 2 O 3 reaction [31] should be revised, as both our ab initio results and the experimental works of Back and Yokota [32] and Hack et al [33] predict that the reactivity of OH with ozone is higher than with NH 2 . A more rigorous critical evaluation of the results obtained here, however, indicates that although CCSD(T)//MP2 results agree fairly well with experimental data, the error introduced by the UMP2 ZPE of the ozone molecule makes CCSD(T)//QCISD results more reliable, especially when large basis sets are employed in both the single-point CCSD(T) energy calculations and the QCISD optimizations.…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…Therefore, this work gives us further indication that the experimental results obtained on the kinetic study of the NH 2 O 3 reaction [31] should be revised, as both our ab initio results and the experimental works of Back and Yokota [32] and Hack et al [33] predict that the reactivity of OH with ozone is higher than with NH 2 . A more rigorous critical evaluation of the results obtained here, however, indicates that although CCSD(T)//MP2 results agree fairly well with experimental data, the error introduced by the UMP2 ZPE of the ozone molecule makes CCSD(T)//QCISD results more reliable, especially when large basis sets are employed in both the single-point CCSD(T) energy calculations and the QCISD optimizations.…”
mentioning
confidence: 72%
“…In our previous ab initio work on the mechanism of the NH 2 O 3 reaction [31] we pointed out this discrepancy and suggested that the experimental data should be revised. The calculations carried out in the present work on the isoelectronic OH O 3 system support this conclusion, because the barriers obtained at the same level of theory are always significantly lower for the OH O 3 reaction.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…In the atmosphere the radicals can in principle react with O 2 , NO, NO 2 or O 3 . The amino radical NH 2 [2,59] and also the N(CH 3 ) 2 radical [60] are known to react only slowly with O 2 , therefore, the atmospheric fate of the amino radicals in moderately polluted atmospheres is potentially reactions with NO, NO 2 and O 3 , as discussed in the literature, [2,59,60] with formation of nitrosamine and nitramine.…”
Section: Amide Atmospheric Oxidation Productsmentioning
confidence: 99%